(untitled) (Journal of the College of Basic Education, 2022)
This paper endeavors to introduce the major "Arabo-Islamic" thinkers in the areas of ’morpho- phonology" and "phonetics". It tries to set their works in this field in comprehensive and mature historical and scientific contexts. The present study investigates the works of some the "Arabo-Islamic" thinkers and their efforts. It starts with morpho-phonology ( ‛ ilm al-taṣriif ) which is unquestionably interrelated with phonetics. They are central in terms of enduring social and intellectual influence on the overall cultural system of Classical Islam. The study is devoted to the second field that includes morphology, which defines the structure of words, phonology, which describes the variations within this structure, and phonetics, which is most often treated when studying one phonological process, germination ( ’ idghaam ). It also focuses upon study of phonetics with the school of lexicology and its pioneer which studies the arrangement of sounds within the mouth and nasal cavities in a step that forms phonetically-based dictionaries. It moves to the grammarians and the phoneticians and their research of Arabic sounds; their properties, divisions into different classes or groups, the relation of sounds to meanings, etc. Remitters of the Quran have effectively participated in areas of places and manners of articulation of sounds, accuracy of pronunciation, mastering sounds in connected speech, variation in pronouncing sounds, etc.